Beyond the Conservation Project. 20th Century Restoration of the Basilica of Santa Maria Maggiore in Tuscania (VT) - Chiara Circo; Luciano Antonino Scuderi (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2023)
The basilica of Santa Maria Maggiore in Tuscania is a medieval building subjected to different interventions over the centuries and long periods of neglect. The current image of the church is the result of the restorations carried out between the 1950s and the 1970s, which had the intention of restoring an image of the church that is the translation on site of an ideal model not always backed up by reliable data. All this was achieved by taking advantage first of post-war reconstruction funds, and then of funding for reconstruction after the 1971 earthquake in Tuscania. The ideal models were the drawings by Luigi Leporini, an architect from Ascoli who worked for the Soprintendenza dei Monumenti del Lazio from 1939 onwards. The paper describes the interventions carried out since an analysis of iconographic and documentary sources, both published and unpublished, and a subsequent direct comparison with the building. The analysis of the restoration sites allows us to investigate the construction methods used to consolidate the masonry buildings in the second half of the 20th century and, at the same time, sheds light on the persistence of the desire to reacquire a hypothetical original image. The study adds new elements to the construction history of the church. Finally provides some general considerations on an approach to the restoration of monuments which tries to find a difficult balance between structural reasons and instances of reconfiguration, which, even in the 1970s, were based on analogical comparison.